Effect of anti-HCV positifity on response to hepatitis B virus vaccine in haemodialysis patients - Ali KOŞAR; Mahmut DALMAZ; Şerife SAĞMANLIGİL and Mehdi YEKSAN and Süleyman TÜRK (Turkish Journal of Gastroenterology, 2019)
-